2003
DOI: 10.1016/s0197-4580(02)00062-3
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of hippocampal neuron numbers in aged rhesus monkeys

Abstract: Preservation of hippocampal neuron numbers in aged rhesus monkeys Keuker, J.I.H.; Luiten, P.G.M.; Fuchs, E. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. AbstractTo invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 65 publications
7
79
3
1
Order By: Relevance
“…Interestingly, the average of 11.3 million granule cells in foxes is similar to what has been found in rhesus monkeys (Keuker et al, 2003), pigs (Holm and West, 1994) and in some human data (Korbo et al, 2004), despite its' much smaller overall brain size. On the other hand, the number of large granule cells correlates with neurogenesis but not with total granule cell number.…”
Section: Resident Granule Cells and Their Relation To Neurogenesissupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, the average of 11.3 million granule cells in foxes is similar to what has been found in rhesus monkeys (Keuker et al, 2003), pigs (Holm and West, 1994) and in some human data (Korbo et al, 2004), despite its' much smaller overall brain size. On the other hand, the number of large granule cells correlates with neurogenesis but not with total granule cell number.…”
Section: Resident Granule Cells and Their Relation To Neurogenesissupporting
confidence: 76%
“…calculated from BrdU positive cells after one injection and three week of survival time (Kozorovitskiy et al, 2005;Leuner et al, 2007) or ~0.02% in Rhesus monkeys (Macaca mulatta, after one to five BrdU injections and variable survival times (Gould et al, 1999;Keuker et al, 2003). Although the primate data has been derived using another marker, this difference alone is unlikely to explain the at least 10-fold differences in the normalized proliferation rates when compared to rodents.…”
Section: Amount To ~004% Of the Number Of Granule Cells In Adult Marmentioning
confidence: 99%
“…Indeed, recent reports using modern stereological cell-counting methods did not show any significant agerelated loss of hippocampal neurons in rats [44], mice [13], monkeys [30,41], or humans [51]. Peters and Sethares reported that even with significant thinning with age of cortical layer 1, accompanied by a loss of some dendrites and spines and a decrease in the frequency of synapses, in the occipital and prefrontal cortex in Rhesus monkeys, there was no significant age-related changes in the number of neurons, astrocytes, or microglia and oligodendrocytes in the layer [42].…”
Section: Discussionmentioning
confidence: 97%
“…When unbiased stereological methods are applied, there are no age-dependent differences in neuronal number or density in the subiculum, CA1, CA2, CA3, DG, and EC in rhesus monkeys Amaral 1993;Rapp 1995;Peters et al 1996;Gazzaley et al 1997;Merrill et al 2000;Keuker et al 2003). Although based on a small number of monkeys, there is no evidence for a relationship between DNMS scores and neuronal numbers in these regions Rapp 1995).…”
Section: Neurons Of the Hippocampus And Related Cortical Regionsmentioning
confidence: 98%